The Catholic Church in the highlands: Five decades of pastoral work in the Ayaviri prelature (1959-2005) - Estenós Loayza, Alejandro (2009)
Based on ecclesiastical primary sources, this paper proposes a sequence of four historical stages of pastoral practice in the Prelature of Ayaviri, an important diocese in the southern Andes of Peru. The determinate phases in a period of almost fifty years are: 1) traditional-conservative (1959-1969); 2) indigenous-cultural (1970-1974); 3) politicalliberationist (1975-1992); and 4) political-democratizing (1993-2005). This analysis points out important changes in pastoral efforts and their implications for the Church’s work in religious (sacramental, liturgical, catechismal or popular religious practices) and social-political terms.